Representasi Masyarakat Kabupaten Tegal Pada Lirik Lagu Galawi Gubahan Agus Riyanto Karya Imam Joend - Arsy Mulana Zulfa; Diryo Suparto; Ike Desi Florina (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This study discusses the Tegalan song entitled Galawi by Imam Joend, through markers and markers to prove the representation of the people of Tegal Regency from the Galawi song. As a scalpel using Ferdinand de Sausure's semiotic theory, in this theory there is a sign is the song Galawi, signifier is song lyrics and signified is a social condition. In this study using descriptive qualitative research methods, by directly interviewing the main sources, namely songwriters and supported by cultural figures to find out the social conditions associated with the lyrics of the song Galawi. Based on the research conducted, it was found the song Galawi. The people of Tegal Regency are stated in the lyrics of the Galawi song, seen from regional identity, social interaction, livelihood, education as well as traditions and culture. The people of Tegal Regency have a fairly good personality, are polite, welcome and entertain guests from outside well and a peaceful and peaceful society. Many people in Tegal Regency still carry out ancestral cultural traditions as a form of gratitude to God Almighty.